Production process of integrated supporting copper powder column and VC vapor chamber

Through the integrated supporting copper powder column production process, the problem of collapse and fall off of the support column is solved, the stability and thermal conductivity of the support column are improved, the heat dissipation needs of high-power consumption equipment are met, and the service life of the VC heat-efficient plate is extended.

CN120533097APending Publication Date: 2025-08-26DONGGUAN RUIJIA NEW MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510676329.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-24
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

After the height of the support columns manufactured by conventional production methods increases in the VC heat-smoothing plate, they are prone to collapse and fall off, resulting in unstable performance and affecting the heat dissipation effect and service life.

Method used

The integrated supporting copper powder column production process is adopted, through the rational design of the mold structure and the copper column insertion step, the powder making tanks and channels in the powder storage unit are used to fill the mixed powder and insert the copper column for firing, forming a tightly combined support column structure, and optimizing the capillary liquid absorbing core with nano-carbon tubes and other components.

Benefits of technology

It improves the structural stability and thermal conductivity of the support column, enhances the heat dissipation performance and service life of the VC heat-efficient plate, adapts to different height requirements, and meets the heat dissipation needs of high-power consumption equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005417872750000071
    Figure BDA0005417872750000071
  • Figure BDA0005417872750000081
    Figure BDA0005417872750000081
  • Figure BDA0005417872750000091
    Figure BDA0005417872750000091
Patent Text Reader

Abstract

The invention relates to the technical processing field of copper powder columns, in particular to a production process of an integrated supporting copper powder column and a VC vapor chamber, and the production process comprises the following steps that a mold is provided with a plurality of powder containing units, each powder containing unit is provided with a plurality of powder preparing grooves, and the adjacent powder preparing grooves are connected through a channel; the preparation method comprises the following steps: uniformly stirring copper powder, bismuth trioxide, antimony trioxide, silver, rosin resin, an adhesive, carbon nanotubes, a pore forming agent and water to obtain mixed powder; filling the mixed powder into a powder making groove and a channel; inserting the mixed powder into the center of the powder making tank filled with the mixed powder to obtain a pre-fired product; and preheating the pre-fired product in an environment with the temperature of 200-300 DEG C, preserving heat for 40-60 minutes at the temperature of 600-800 DEG C, preserving heat for 2-3 hours at the temperature of 1070-1100 DEG C, cooling to 20-30 DEG C, and demolding to obtain a finished product. Through the design of the powder containing unit of the mold, copper column inserting firing is matched after powder filling, an integrated supporting structure is formed, the overall stability of the supporting column is enhanced, different height requirements are met, collapse and falling are avoided, and the use stability of the vapor chamber is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of copper powder column technology processing, and more specifically, to a production process for an integrated support copper powder column and a VC heat sink. Background Art

[0002] With the rapid development of artificial intelligence (AI), the computing power requirements of various electronic devices have exploded, leading to a significant increase in device power consumption. As a highly efficient heat dissipation component, the VC vapor chamber primarily transfers heat through the phase change of the internal working fluid, effectively dissipating heat from high-heat-generating components in electronic devices.

[0003] Conventional VC vapor chambers, in response to current high power consumption, are finding it increasingly difficult to meet heat dissipation requirements due to their inherent structural design and material application. This is primarily due to the fact that as power consumption increases, the thickness of the VC vapor chamber must be increased to enhance heat dissipation, which in turn increases the volume of the chamber housing key components such as the working fluid and capillary wick. Consequently, the height of the support columns within the VC vapor chamber must also be increased to maintain the stability and reliability of the entire structure.

[0004] However, conventional production methods for the increased height of support columns, particularly copper column powder rings, present numerous challenges. During use, the height of the support columns can easily lead to collapse or fall off when subjected to external shocks such as vibration or compression. This can lead to unstable performance during actual use, impacting the VC vapor chamber's cooling performance and service life. Summary of the Invention

[0005] In order to solve the problem that the support column height increases, it is easy to collapse and fall off, affecting production and heat dissipation performance, the present application provides an integrated support copper powder column production process and a VC heat sink.

[0006] In a first aspect, the present application provides a production process for an integrated support copper powder column, which adopts the following technical solution: a production process for an integrated support copper powder column, comprising the following steps: Prepare the mold: The mold is provided with a plurality of powder placement units, each of which is provided with a plurality of powder making troughs, wherein adjacent powder making troughs are connected by channels, and the height of the channels is lower than that of the powder making troughs; Prepare mixed powder: mix copper powder, bismuth trioxide, antimony trioxide, silver, rosin resin, binder, carbon nanotubes, pore-forming agent, and water to obtain mixed powder; Powder loading: filling the mixed powder into the powder making tank and the channel; Inserting a copper pillar: inserting a copper pillar of the same height into the center of the powder making tank filled with mixed powder, and removing excess mixed powder to obtain a pre-fired product; Firing: The pre-fired product is placed in an environment with a temperature of 200-300℃ for preheating for 1-2h, then heated to 600-800℃ at a rate of 10-20℃ / min, kept warm for 40-60min, then heated to 1070-1100℃ at a rate of 5-10℃ / min, kept warm for 2-3h, then cooled to 20-30℃ at a rate of 10-20℃ / min, demoulded, and the finished product is obtained.

[0007] By adopting the above technical solution, through a rationally designed mold structure, utilizing the powder preparation trough and channel in the powder placement unit, and inserting the copper pillars after filling the mixed powder, the support pillars can be effectively prevented from collapsing and falling off during production use. This process involves filling the mixed powder into the powder preparation trough and channel, inserting the copper pillars, and firing them. This allows the support pillars to tightly bond with the surrounding copper powder during the firing process, forming a one-piece structure. This integrated design allows the materials surrounding the support pillars to support each other and jointly withstand external forces, significantly improving the overall stability of the support pillars. This effectively prevents the support pillars from collapsing and falling off, and ensures the stability of the VC vapor chamber during actual use.

[0008] This process can accommodate support pillar production requirements of varying heights. By rationally adjusting the mold's powder-making tank and channel dimensions, as well as the copper pillar insertion height, support pillars of appropriate heights can be flexibly produced to meet the varying thickness requirements of VC vapor chambers. This allows the VC vapor chamber to better meet the heat dissipation requirements of high-power devices while maintaining structural stability.

[0009] The increased stability of the support columns better maintains the integrity and uniformity of the wick throughout the VC vapor chamber. Components like carbon nanotubes in the powder mix interact with other materials during the firing process, helping to form a denser, more efficient capillary wick structure. This optimized wick more effectively absorbs and transfers the working fluid, thereby enhancing the VC vapor chamber's heat dissipation performance. This allows it to dissipate heat more quickly when working with high-power devices, ensuring proper operation.

[0010] During the firing process, the copper pillars bond tightly with the surrounding powder mixture, giving them not only excellent mechanical support but also serving as thermal conduits, transferring heat more quickly to all parts of the VC vapor chamber. Furthermore, the highly thermally conductive metal components in the powder mixture, such as copper and silver, form a dense structure after firing, further increasing the thermal conductivity of the entire support pillar and promoting rapid heat transfer, thereby effectively enhancing the overall heat dissipation of the VC vapor chamber and meeting the needs of high power consumption.

[0011] During the sintering process, treatment at different temperature stages plays a key role in the structure and capillary performance of the support pillars. During the preheating stage at 200-300°C, some volatile components in the mixed powder, such as rosin resin, can be removed. This helps to reduce defects that may occur during the subsequent sintering process. During the insulation stage at 600-800°C, the copper powder begins to sinter, and the connection between the particles gradually strengthens. At the same time, components such as carbon nanotubes also form a stable bond with the copper powder. During the high-temperature sintering stage at 1070-1100°C, the densification of the support pillars is further improved, but it does not become overly dense and clog the pores. The appropriate sintering time and temperature can ensure good pore connectivity and an appropriate pore size, providing a suitable structural foundation for capillary action, facilitating liquid flow, and improving heat dissipation.

[0012] Preferably, the weight percentages of the various components in the mixed powder are as follows: Copper powder 80-85% Bismuth trioxide 0.5-1% Antimony trioxide 0.5-1% Silver 1-2% Rosin resin 3-6% Adhesive 1-2% Carbon nanotubes 1-5% Pore ​​forming agent 0.5-1% The balance is water.

[0013] By adopting the above technical solution, using a specific ratio of each component, and then forming an integrated supporting copper powder column through a sintering process, the structural stability, thermal conductivity and capillary action of the support column are significantly improved, solving the problem of the support column in the high-power VC heat spreader being prone to collapse and falling off, and improving the heat dissipation effect and service life.

[0014] Preferably, the copper powder is composed of copper powder with an average particle size of 0.01-0.1 μm, copper powder with an average particle size of 0.2-1 μm and copper powder with an average particle size of 1.1-2 μm in a weight ratio of (4-6): (2-3): 1.

[0015] By adopting the above technical solution, the average particle size and weight ratio of the copper powder are optimized. During sintering, the small-particle copper powder can fill the gaps between the large-particle copper powder, making the contact between the copper powder closer, increasing the density and strength after sintering, and thus enhancing the structural stability of the supporting copper powder column, making it less likely to deform or be damaged during use in high-power VC heat sinks.

[0016] At the same time, the uneven pore structure formed by mixing copper powders of varying particle sizes improves the adsorption and transmission of the working fluid. The fine pores formed by small-particle copper powder increase the specific surface area and enhance the adsorption capacity of the working fluid. The larger pores formed by medium- and large-particle copper powders facilitate the rapid flow of the working fluid, thus creating a good capillary effect, promoting the circulation of the working fluid within the supporting copper powder columns and improving heat dissipation performance.

[0017] Preferably, the pore-forming agent is composed of hydroxypropyl methylcellulose and sodium bicarbonate in a weight ratio of (3-6):2.

[0018] Hydroxypropyl methylcellulose has good thermal stability and provides structural support during the initial stages of sintering, preventing powder collapse. Sodium bicarbonate decomposes during the initial stages of sintering to produce carbon dioxide gas, forming a large number of tiny pores. These pores increase the specific surface area of ​​the copper powder columns, enhancing their adsorption capacity for the working fluid, strengthening the capillary action, accelerating the circulation of the working fluid, and improving heat dissipation efficiency. Simultaneously, hydroxypropyl methylcellulose carbonizes at high temperatures to form a carbon skeleton, which, after sintering with the copper powder, forms a composite structure. This maintains pore connectivity while enhancing mechanical strength, preventing pore collapse, ensuring long-term stable heat dissipation, and extending the service life of the VC heat spreader. The synergistic effect of these two components optimizes the internal pore structure and performance of the copper powder columns.

[0019] The coordinated use of the two can form a large number of uniform, small and well-connected pores inside the supporting copper powder column, enhance the capillary action, promote the circulation of the working fluid and improve the heat dissipation performance.

[0020] Preferably, the adhesive comprises at least one of polyvinyl alcohol, polyacrylic acid, povidone and polyethylene glycol.

[0021] By adopting the above technical solution and optimizing the type of binder, the copper powder, bismuth trioxide, antimony trioxide, and silver components can be tightly bonded together, improving the cohesion of the mixed powder and preventing loosening and shedding of particles during the filling and sintering processes. Its good water solubility also facilitates the mixing of the mixed powder and demolding after molding, helping to improve production efficiency.

[0022] Preferably, the carbon nanotubes have a diameter of 300-500 nm and a length of 1-2 μm.

[0023] By adopting the above technical solution and optimizing the diameter and length of carbon nanotubes, the mechanical strength and compressive resistance of the supporting copper powder columns can be effectively improved, ensuring their stable support structure in high-power VC heat spreaders and preventing deformation or damage due to thermal or mechanical stress. At the same time, an efficient heat conduction network is formed in the copper powder matrix. It can quickly transfer heat from high-temperature areas to low-temperature areas, thereby improving the overall thermal conductivity of the supporting copper powder columns and enhancing the heat dissipation effect of the VC heat spreader. During the sintering process, this carbon nanotube can act as a skeleton to prevent excessive sintering of copper powder particles, which would lead to a decrease in porosity. Its good thermal stability enables it to maintain structural integrity even at high temperatures, helping to form uniform and dense supporting copper powder columns and improve the overall performance of the product.

[0024] Preferably, the rosin resin is esterified rosin resin and / or maleic acid rosin resin.

[0025] By adopting this technical solution, the mixed powder maintains its shape during the filling and sintering process, preventing loose particles. Furthermore, after decomposition, pores are left within the supporting copper powder columns, which synergize with the pore-forming agent to form a uniform, fine, and well-connected pore structure, enhancing capillary action and promoting circulation of the working fluid.

[0026] Preferably, the copper pillars are pretreated in the copper pillar inserting step: The surface of the copper column was polished using sandpaper of different grits, with 600-800 grit sandpaper used for coarse polishing, and then gradually fine polished using 1000-1200 grit sandpaper to obtain a pretreated copper column with a surface Ra of 0.2-0.4 μm.

[0027] This technical solution facilitates the mechanical anchoring of the powder mixture onto the copper pillar surface, tightly bonding the copper pillar to the powder mixture and preventing delamination or shedding during use. This improves the integrity and stability of the supporting copper powder pillars. During sintering, a more uniform interface is formed between the copper pillars and the powder mixture, promoting sintering densification, increasing the density and strength of the supporting copper powder pillars, and enhancing their creep resistance and thermal stability under high-temperature conditions.

[0028] Furthermore, a uniform surface roughness helps the powder mix form a more even coating on the copper pillars, creating a more balanced pore structure within the supporting copper pillars. This facilitates the circulation of the working fluid, enhances capillary action, and improves heat dissipation efficiency. Furthermore, a well-bonded interface reduces thermal resistance, allowing heat to be more efficiently transferred from the copper pillars to the powder mix, thereby enhancing the heat dissipation performance of the entire VC vapor chamber.

[0029] Preferably, the mold is a graphite mold.

[0030] Graphite molds have excellent thermal conductivity, transferring heat quickly and evenly. This ensures uniform heating of the powder mixture during sintering, ensuring a uniform and dense internal structure within the supporting copper powder columns and improving product quality. Their low coefficient of thermal expansion ensures dimensional stability at high temperatures, ensuring the dimensional and shape accuracy of the supporting copper powder columns. Furthermore, graphite molds are chemically stable and resist chemical reactions with the copper powder and other components during high-temperature sintering, preventing the introduction of impurities and ensuring the purity and performance of the supporting copper powder columns.

[0031] In a second aspect, the present application provides a VC vapor chamber, which adopts the following technical solution: A VC vapor chamber, comprising an outer shell structure and an internal structure, wherein the outer shell structure comprises an upper shell and a lower shell, the upper shell and the lower shell being sealed and welded together to form a sealed cavity; The internal structure includes a capillary wick and an integrated supporting copper powder column and a supporting column. The capillary wick covers the inner surface of the upper shell and the lower shell. The capillary wick is provided with a placement groove for placing the integrated supporting copper powder column. The supporting columns are distributed inside the capillary wick or between the capillary wick and the outer shell, and are evenly distributed inside the cavity of the VC heat spreader according to a certain spacing and arrangement. The integrated supporting copper powder column is produced by the production process of the integrated supporting copper powder column described in the first aspect.

[0032] The upper and lower shells are sealed and welded to form a closed cavity, ensuring that the working fluid inside the VC heat spreader will not leak, maintaining its normal heat dissipation function. Good sealing also helps prevent external contaminants from entering the cavity and affecting the internal structure and performance, thereby improving the reliability and durability of the product. The support columns are distributed inside the capillary core or between the capillary core and the outer shell, and are evenly distributed according to a certain spacing and arrangement, which enhances the overall structural stability of the VC heat spreader. The integrated supporting copper powder column is made through a special process and has high strength and stability. It can withstand thermal and mechanical stress under high power consumption conditions, prevent the VC heat spreader from deformation or damage, and extend its service life. The capillary core covers the inner surface of the upper and lower shells, and the placement groove inside it is used to place the integrated supporting copper powder column. This structural design allows the supporting copper powder column to be tightly combined with the capillary core.

[0033] The integrated copper powder support columns offer excellent thermal conductivity and capillary action, rapidly transferring heat from the evaporation zone to the condensation zone, promoting the circulation of the working fluid and improving heat dissipation efficiency. Furthermore, the even distribution of the copper powder support columns ensures uniform heat transfer within the VC vapor chamber, preventing localized overheating. The capillary wick features a placement slot for the integrated copper powder support columns. This design utilizes internal space, organically integrating the support and wick structures, improving space efficiency while ensuring the VC vapor chamber's lightweight design, meeting the requirements of modern electronic devices for miniaturized and high-performance heat dissipation components.

[0034] In summary, this application has the following beneficial effects: 1. Improved structural stability: The powder placement unit design of the mold, combined with the copper pillars inserted and fired after powder loading, forms an integrated support structure, enhancing the overall stability of the support pillars, adapting to different height requirements, avoiding collapse and falling, and ensuring the stability of the heat spreader.

[0035] 2. Optimized heat dissipation: During firing, the copper pillars are tightly bonded to the powder mixture, providing both mechanical support and thermal conductivity. Ingredients like carbon nanotubes in the powder mixture form a dense capillary wick, while copper powder and silver enhance thermal conductivity, accelerating heat transfer and enhancing heat dissipation, meeting the cooling needs of high-power devices.

[0036] 3. Strong production adaptability: By adjusting the mold size and the copper column insertion height, support columns of heat sinks of different thicknesses can be flexibly produced to meet diverse heat dissipation needs. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 Schematic diagram of the structure of the graphite mold in Example 1; Figure 2 Application Example 1: Explosion-proof photo of a VC vapor chamber; Figure 3 Schematic diagram of the structure of the integrated support copper powder column; Figure numerals: 1. powder placing unit; 2. powder making tank; 3. channel; 4. upper shell; 5. lower shell; 6. capillary wick; 7. integrated supporting copper powder column; 8. supporting column; 9. placing tank. DETAILED DESCRIPTION Example

[0038] The esterified rosin resin is DRT Dertoline G2L glycerol esterified rosin.

[0039] Maleic rosin resin was purchased from Guangxi Wuzhou Richeng Forest Products Chemical Co., Ltd., model MR-115.

[0040] Example 1 A production process for an integrated support copper powder column comprises the following steps: Prepare mold: Use graphite mold, such as Figure 1 As shown, the graphite mold is provided with a plurality of powder placing units, and the placing units are provided with a plurality of powder making grooves. Adjacent powder making grooves are connected by channels, and the height of the channels is lower than that of the powder making grooves. Prepare mixed powder: 80g copper powder (average particle size 0.1μm), 1g bismuth trioxide, 1g antimony trioxide, 2g silver, 6g rosin resin (esterified rosin resin), 1g binder (polyvinyl alcohol), 5g carbon nanotubes, 0.5g pore-forming agent, and 3.5g water were mixed uniformly to obtain mixed powder; The pore-forming agent is composed of hydroxypropyl methylcellulose and sodium bicarbonate in a weight ratio of 3:2; The diameter of the carbon nanotube is 300nm and the length is 1μm.

[0041] Powder loading: Fill the mixed powder into the powder making tank and channel; Inserting copper pillars: inserting a copper pillar of the same height into the center of the powder making tank filled with mixed powder, and removing excess mixed powder to obtain a pre-fired product; Firing: The pre-fired product is placed in an environment with a temperature of 200℃ for preheating for 1h, then heated to 600℃ at a rate of 10℃ / min, kept warm for 40min, then heated to 1070℃ at a rate of 5℃ / min, kept warm for 2h, then cooled to 20℃ at a rate of 10℃ / min, demolded, and the finished product is obtained.

[0042] The difference between Example 2-3 and Example 1 is that the parameters of the production process of the integrated support copper powder column, the types of raw materials and the amounts used are different. The specific differences are shown in Table 1: Table 1 Parameters, raw material types and amounts of the production process of the integrated support copper powder column of Examples 1-3 Example 4 A production process for an integrated supporting copper powder column. The difference between this embodiment and embodiment 1 is that the copper powder is composed of copper powder with an average particle size of 0.01 μm, copper powder with an average particle size of 0.2 μm, and copper powder with an average particle size of 1.1 μm in a weight ratio of 4:2:1.

[0043] Example 5 A production process for an integrated supporting copper powder column. The difference between this embodiment and embodiment 1 is that the copper powder is composed of copper powder with an average particle size of 0.1 μm, copper powder with an average particle size of 1 μm, and copper powder with an average particle size of 2 μm in a weight ratio of 6:3:1.

[0044] Example 6 A production process for an integrated support copper powder column. The difference between this embodiment and embodiment 1 is that the pore-forming agent is hydroxypropyl methylcellulose.

[0045] Example 7 A production process for an integrated support copper powder column. The difference between this embodiment and embodiment 1 is that the copper column is pretreated in the copper column inserting step: The surface of the copper column was polished using sandpaper of different grits, coarsely polished using 600-grit sandpaper, and then finely polished using 1000-grit sandpaper step by step, to obtain a pretreated copper column with a surface Ra of 0.2 μm.

[0046] Example 8 A production process for an integrated support copper powder column. The difference between this embodiment and embodiment 1 is that the copper column is pretreated in the copper column inserting step: The surface of the copper column was polished using sandpaper of different grits, coarsely polished using 800-grit sandpaper, and then finely polished using 1200-grit sandpaper step by step, to obtain a pretreated copper column with a surface Ra of 0.4 μm.

[0047] Comparative Example Comparative Example 1 A production process for an integrated supporting copper powder column. The difference between this comparative example and Example 1 is that the copper column inserting step is omitted.

[0048] Comparative Example 2 A production process for an integrated supporting copper powder column. The difference between this comparative example and Example 1 is that the preheating temperature in the firing step is 100°C.

[0049] Comparative Example 3 A production process for an integrated supporting copper powder column. The difference between this comparative example and Example 1 is that nano-ceramic powder is used instead of carbon nanotubes in the step of preparing the mixed powder.

[0050] Comparative Example 4 A production process for an integrated supporting copper powder column. The difference between this comparative example and Example 1 is that nano-ceramic powder is used instead of antimony trioxide.

[0051] Comparative Example 5 A production process for an integrated supporting copper powder column. The difference between this comparative example and Example 1 is that nano-ceramic powder is used instead of bismuth trioxide.

[0052] Comparative Example 6 A production process for an integrated supporting copper powder column. The difference between this comparative example and Example 1 is that no phenolic resin is added.

[0053] Phenolic resin was purchased from Wuhan Jiyesheng Chemical Co., Ltd., model PF131.

[0054] Application Examples Application Example 1 A VC heat sink, VC heat sink shell structure and internal structure, refer to Figure 2 The outer shell structure includes an upper shell 4 and a lower shell 5, and the upper shell 4 and the lower shell 5 are sealed and welded together to form a closed cavity; Reference Figure 2 and Figure 3 The internal structure includes a capillary wick 6 and an integrated supporting copper powder column 7 and a supporting column 8. The capillary wick 6 covers the inner surface of the upper shell 4 and the lower shell 5. The capillary wick 6 is provided with a placement groove 9 for placing the integrated supporting copper powder column 7. The supporting columns 8 are distributed inside the capillary wick 6 or between the capillary wick 6 and the outer shell, and are evenly distributed inside the cavity of the VC heat spreader according to a certain spacing and arrangement. The integrated supporting copper powder column is from the integrated supporting copper powder column of Example 1.

[0055] The difference between Application Example 2-14 and Application Example 1 is that the sources of the integrated supporting copper powder columns are different. The specific differences are shown in Table 2: Table 2 Sources of the integrated copper powder columns in Application Examples 1-14 Detection method / test method Thermal conductivity test: refer to GB / T 22588-2008.

[0056] Porosity: Use the volume method to test the porosity. Prepare 200 ml of water, place the integrated support copper powder column in the water, let it stand for 30 minutes, take it out, and measure the volume of water again to calculate the porosity. Porosity = (V0-V1) / V0, where V0 is the initial volume of water and V1 is the volume after water absorption.

[0057] Shock resistance test: Using a shock test bench that complies with GB / T 2423.8, the vapor chamber was fixed on the shock test bench and subjected to half-sine wave shocks in the X, Y, and Z axes, with an acceleration of 50g and a pulse duration of 11ms. Each axis was subjected to 1000 shocks. After the shock test, the unit was disassembled and the integrated copper powder support pillars were inspected for deformation, cracks, or shedding. The experimental data is shown in Table 3: Table 3 Experimental data of Examples 1-8 and Comparative Examples 1-6 Comparative Examples 2-6 all experienced varying degrees of problems during impact testing, such as deformation, cracking, and shedding. The impact test results for Example 1 showed no deformation, cracking, or shedding, demonstrating that the integrated copper powder support pillar production process significantly improves the structural stability of the support pillars. This is crucial for the reliability of VC vapor chambers in practical use and can effectively extend their service life.

[0058] Although the thermal conductivity of Comparative Example 1 is as high as 1897W / m·K, its impact resistance test performed poorly, with problems such as deformation, cracking, and falling off. This shows that although high thermal conductivity is generally regarded as an advantage, if the structural stability of the support column is insufficient, high thermal conductivity cannot play its advantages in practical applications. The production process of the integrated support copper powder column in this application can achieve a good balance between thermal conductivity, porosity and impact resistance. This balance not only improves the heat dissipation performance of the product, but also significantly enhances its structural stability, enabling it to better cope with the heat dissipation needs of high-power consumption equipment and extend the service life of the product.

[0059] The experimental data from Examples 1 and 4-5 demonstrate that by adjusting the copper powder particle size, Examples 4 and 5 outperform Example 1 in both thermal conductivity and porosity without compromising impact resistance. This demonstrates the importance of optimizing copper powder particle size in improving the performance of integrated support copper powder pillars. The synergistic effect of copper powders of varying particle sizes not only improves the microstructure and thermal conductivity but also optimizes porosity, providing enhanced support for heat dissipation and structural stability of the VC vapor chamber.

[0060] From the experimental data of Example 1 and Example 6, it can be seen that optimizing the type and amount of the pore-forming agent helps to form a more uniform and appropriate pore structure, thereby improving the thermal conductivity.

[0061] It can be seen from the experimental data of Example 1 and Examples 7-8 that by optimizing the surface roughness of the copper pillars, the heat conduction efficiency between the copper pillars and the mixed powder can be enhanced, and at the same time, the impact resistance of the product can be further enhanced.

[0062] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed, but as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A production process for an integrated support copper powder column, characterized in that: The following steps are involved: Prepare the mold: The mold is provided with a plurality of powder placement units, each of which is provided with a plurality of powder making troughs, wherein adjacent powder making troughs are connected by channels, and the height of the channels is lower than that of the powder making troughs; Prepare mixed powder: mix copper powder, bismuth trioxide, antimony trioxide, silver, rosin resin, binder, carbon nanotubes, pore-forming agent, and water to obtain mixed powder; Powder loading: filling the mixed powder into the powder making tank and the channel; Inserting a copper pillar: inserting a copper pillar of the same height into the center of the powder making tank filled with mixed powder, and removing excess mixed powder to obtain a pre-fired product; Firing: The pre-fired product is placed in an environment with a temperature of 200-300℃ for preheating for 1-2h, then heated to 600-800℃ at a rate of 10-20℃ / min, kept warm for 40-60min, then heated to 1070-1100℃ at a rate of 5-10℃ / min, kept warm for 2-3h, then cooled to 20-30℃ at a rate of 10-20℃ / min, demoulded, and the finished product is obtained.

2. The production process of an integrated support copper powder column according to claim 1, characterized in that: The weight percentages of the various components in the mixed powder are as follows: Copper powder 80-85% Bismuth trioxide 0.5-1% Antimony trioxide 0.5--1% Silver 1-2% Rosin resin 3-6% Adhesive 1-2% Carbon nanotubes 1-5% Pore ​​forming agent 0.5-1% The balance is water.

3. The production process of an integrated support copper powder column according to claim 2, characterized in that: The copper powder is composed of copper powder with an average particle size of 0.01-0.1 μm, copper powder with an average particle size of 0.2-1 μm and copper powder with an average particle size of 1.1-2 μm in a weight ratio of (4-6): (2-3):

1.

4. The production process of an integrated support copper powder column according to claim 1, characterized in that: The pore-forming agent is composed of hydroxypropyl methylcellulose and sodium bicarbonate in a weight ratio of (3-6):

2.

5. The production process of an integrated support copper powder column according to claim 1, characterized in that: The binder includes at least one of polyvinyl alcohol, polyacrylic acid, povidone and polyethylene glycol.

6. The production process of an integrated support copper powder column according to claim 1, characterized in that: The carbon nanotubes have a diameter of 300-500 nm and a length of 1-2 μm.

7. The production process of an integrated support copper powder column according to claim 1, characterized in that: The rosin resin is esterified rosin resin and / or maleic acid rosin resin.

8. The production process of an integrated support copper powder column according to claim 1, characterized in that: Pre-treat the copper pillars during the copper pillar insertion step: The surface of the copper column was polished using sandpaper of different grits, with 600-800 grit sandpaper used for coarse polishing, and then gradually fine polished using 1000-1200 grit sandpaper to obtain a pretreated copper column with a surface Ra of 0.2-0.4 μm.

9. The production process of an integrated support copper powder column according to claim 1, characterized in that: The mold is a graphite mold.

10. A VC heat sink, characterized in that: The VC heat spreader shell structure and internal structure, the shell structure includes an upper shell and a lower shell, the upper shell and the lower shell are sealed and welded together to form a closed cavity; The internal structure includes a capillary wick and an integrated supporting copper powder column and a supporting column. The capillary wick covers the inner surface of the upper shell and the lower shell. The capillary wick is provided with a placement groove for placing the integrated supporting copper powder column. The supporting columns are distributed inside the capillary wick or between the capillary wick and the outer shell, and are evenly distributed inside the cavity of the VC heat spreader according to a certain spacing and arrangement. The integrated supporting copper powder column is produced by the production process of the integrated supporting copper powder column described in any one of items 1-9.

Citation Information

Cited By

  • Preparation method of cold plate, cold plate and two-phase heat exchanger

    CN122210052A